2004
DOI: 10.1111/j.1365-2567.2004.01975.x
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the B‐cell inhibitory protein factor in Ixodes ricinus tick saliva: a potential role in enhanced Borrelia burgdoferi transmission

Abstract: SUMMARYWe recently described the inhibition of host B lymphocytes by Ixodes ricinus tick saliva. In this study, we characterized the factor responsible for this activity and examined the modulation of lipopolysaccharide (LPS)-and Borrelia burgdorferi outer surface protein (Osp)-induced proliferation of naive murine B lymphocytes by an enriched fraction of this factor. The B-lymphocyte inhibitory activity was destroyed by trypsin treatment, indicating that a proteinaceous factor was responsible for this activit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
50
0
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(51 citation statements)
references
References 30 publications
0
50
0
1
Order By: Relevance
“…One microgram of total RNA was reverse transcribed using oligo(dT) [12][13][14][15][16][17][18] and Superscript II reverse transcriptase (GIBCO-Invitrogen). Quantitative real-time PCR was performed in a Bio-Rad (Hercules, CA) iCycler with Bio-Rad iQ SYBR green Supermix.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…One microgram of total RNA was reverse transcribed using oligo(dT) [12][13][14][15][16][17][18] and Superscript II reverse transcriptase (GIBCO-Invitrogen). Quantitative real-time PCR was performed in a Bio-Rad (Hercules, CA) iCycler with Bio-Rad iQ SYBR green Supermix.…”
Section: Methodsmentioning
confidence: 99%
“…Especially for ticks, which are characterized by their extended feeding time, a broad repertoire of immune modulatory activities has been described. These modulatory activities include the predominant induction of a Th2 response with an overall inhibition of proinflammatory and Th1 cytokines (23,24,38,54), suppression of the effector functions of antigen-presenting cells (APCs) (5,26,28,59), and modulation of T-cell (28,59) and B-cell (17,18) responses, as well as the inhibition of granulocyte infiltration (39,53) and NK-mediated cytotoxicity (25). Illustrating the importance of salivary components for pathogen transmission, the tick protein Salp15 was shown to significantly increase the infectivity of Borrelia burgdorferi spirochetes in mice (50).…”
mentioning
confidence: 99%
“…During the feeding process, saliva from the tick accompanies the spirochete into the host tissue. Recent findings have provided clear evidence of roles for various tick salivary factors, such as B cell inhibitory protein (64) and sialostatin L (84), among others (98,106,(121)(122)(123), in the localized disruption of host tissues and immune responses. The activity of these salivary factors supports the successful transmission of B. burgdorferi organisms to the host as well as providing a localized environment by which the spirochetes can evade immune clearance.…”
Section: Development Of Arthritis Upon Infection With B Burgdorferimentioning
confidence: 99%
“…It has already been shown that they use Salp15 to inhibit the activation and proliferation of CD4 ϩ T cells by binding to its CD4 receptor (1,6,13). In addition, tick salivary proteins have been found to inhibit B cells (8), dendritic cells (4,11), NK cells (17), neutrophils (20), and macrophages (7). Isac (5,27) and Salp20 (26) are two salivary proteins that were shown to inhibit the alternative pathway of the complement system.…”
Section: Discussionmentioning
confidence: 99%